Pharmacokinetic and pharmacodynamic modelling of continuous erythropoiesis receptor activator in children: a comprehensive analysis and real-world data validation - Mouksassi, Samer; Schaefer, Franz; Warady, Bradley A.; Schmitt, Claus P.; Reigner, Sylvie Meyer; Studer, Milena; Chanu, Pascal; Frey, Nicolas Manuel (British journal of clinical pharmacology, 2025)
Aims To further assess the pharmacokinetic/pharmacodynamic characteristics of methoxy polyethylene glycol-epoetin β (continuous erythropoiesis receptor activator; C.E.R.A.) in children with chronic kidney disease (CKD) aged 3 months to 18 years undergoing different dialysis modalities and receiving intravenous/subcutaneous doses, compared with adults. Methods The population pharmacokinetic and pharmacokinetic/pharmacodynamic C.E.R.A. models, developed using intravenous and subcutaneous data from adults with various dialysis modalities and intravenous data from children receiving haemodialysis, were updated with subcutaneous data from children receiving peritoneal dialysis or predialysis from the phase II paediatric study NH19708 (SKIPPER). Observed and predicted median C.E.R.A. doses and mean haemoglobin levels (indicative of response) were compared using paediatric clinical trials and real-world data from the MH40258 registry study. Results The pharmacokinetic analysis in 627 patients, including 103 children aged 0.5-17 years, revealed that subcutaneous bioavailability in children was 2.18 times higher than in adults (67.1% [95% confidence interval: 52.6-81.6]). Distribution volume increased with weight and age, and clearance increased with weight. Incorporating dialysis modality as a covariate improved the pharmacokinetic/pharmacodynamic model's fit to haemoglobin data. The agreement of observed and predicted paediatric data with real-world data underscores the model's predictive performance and C.E.R.A.’s replicable clinical trial effects in clinical practice. Conclusions This analysis enhanced our knowledge of C.E.R.A.’s effects in children with CKD, confirming its pharmacokinetic/pharmacodynamic characteristics align with adults. Comparison of clinical trial data, model prediction, and real-world data show that C.E.R.A. intravenous and subcutaneous dosing and procedures in adults and children provide adequate control of haemoglobin in clinical practice.